Calibration of Polymers and Characterization - Gabriel, Silvia [UNESP]; Hector, Eugenio [UNESP] (Comite Interamericano Soc Microscopia Electronica-ciasem, 2019)
Characterization of polymeric materials has many levels. The characterization typically has as a goal to improve the performance of the material. As such, many characterization techniques should ideally be linked to the desirable properties of the material such as strength, impermeability, thermal stability, and optical properties. This paper calibrates molecular weight distribution, the molecular structure, the morphology of the polymer, thermal properties, mechanical properties, and any additives.
Keywords: Polymers; Calibration; Characterization